FOR IMMEDIATE RELEASE ATTENTION: POLITICAL EDITOR 801021 - JOHNSON,J (Tufts Archival Research Center, 2007)
Press Release from No on California Proposition 10, which would require no-smoking sections in enclosed public places. Lists prominent members of the coalition opposing the proposition. Argues smoking behavior is "best governed by common sense and courtesy."